In search of lost contracts (regulatory powers of the Secretary of Energy by Law 24,065 and section 9 of Resolution SE 95/13) (Universidad de San Andres Law Review, 2023)
This paper considers the scope of regulatory powers attributed to the Secretary of Energy by Law 24,065. It focuses on Resolution SE 95/2013, particularly in relation to its Section 9. This section provided for the suspension of the right of generators, distributors, and large users to enter into contracts in the electricity market. This suspension, as of date, although was originally referred to as provisional, has extended more than ten years.
Keywords: electricity; regulation; wholesale electricity market; contracts